2020
DOI: 10.1055/s-0040-1707215
|View full text |Cite
|
Sign up to set email alerts
|

Concise Total Synthesis of (+)-Atlanticone C

Abstract: The first enantioselective total synthesis of (+)-atlanticone C is described. The complex tricyclic protoilludane core was rapidly assembled by a photochemical reaction cascade starting from an easily accessible indanone precursor (3 steps). Optimization of an enantioselective Corey–Bakshi–Shibata reduction permitted a catalytic chiral reso­lution of the racemic photoproduct (45% over two steps; up to 98% ee). The enantiomerically enriched photoproduct was efficiently transformed into the (+)-enantiomer of atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The research group later described the first enantioselective total synthesis of (+)-atlanticone C using a similar photochemical reaction cascade. [73] A catalytic chiral resolution of the racemic photoproduct was enabled by an enantioselective Corey-Bakshi-Shibata reduction. This time, (+)-atlanticone C was prepared in 10 steps with 18% yield from the enantiomerically pure photoproduct.…”
Section: Applications Of Ortho Photocycloaddition In Total Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The research group later described the first enantioselective total synthesis of (+)-atlanticone C using a similar photochemical reaction cascade. [73] A catalytic chiral resolution of the racemic photoproduct was enabled by an enantioselective Corey-Bakshi-Shibata reduction. This time, (+)-atlanticone C was prepared in 10 steps with 18% yield from the enantiomerically pure photoproduct.…”
Section: Applications Of Ortho Photocycloaddition In Total Synthesesmentioning
confidence: 99%
“…Product 77 was then obtained with an ee of 96% with the same process used in the (+)-atlanticone C synthesis. [73] The oxazaborolidine 78 was used for a catalytic chiral resolution of the photoproduct 76 by a Corey-Bakshi-Shibata reduction. [76] Finally, (+)-agarozizanol B was obtained from compound 77 after seven steps with an overall yield of 55%.…”
Section: Applications Of Ortho Photocycloaddition In Total Synthesesmentioning
confidence: 99%
“…The relative configurations of all four natural products were assigned by NOESY, while the absolute configuration of atlanticone A (34) was determined by a combination of PM3 calculations and ECD spectral comparison with plorantinone B (24) [43]. Both a racemic synthesis and enantioselective total synthesis of atlanticone C (36) have been reported [44,45].…”
Section: Protoilludane Sesquiterpenesmentioning
confidence: 99%
“…The relative configurations of all four natural products were assigned by NOESY, while the absolute configuration of atlanticone A (34) was determined by a combination of PM3 calculations and ECD spectral comparison with plorantinone B (24) [43]. Both a racemic synthesis and enantioselective total synthesis of atlanticone C (36) have been reported [44,45]. Repraesentin A (38) (Figure 8), a closely related natural product to Δ 6 -protoilludene (7), was isolated from another mushroom from the Lactarius genus, L. repraesentaneus [46].…”
Section: Protoilludane Sesquiterpenesmentioning
confidence: 99%
“…Inspired by the pioneering efforts of Wagner, Gilbert, Hoffmann, and others, our group has studied reaction cascades which are initiated by an ortho -photocycloaddition , to a benzene ring. We found that 7-alkenyloxy-substituted 1-indanones provide a remarkably efficient entry into the protoilludane class of natural products if irradiated at long wavelength (λ > 350 nm) . At shorter wavelength (λ = 350 nm), a third photon initiates a di-π-methane rearrangement reaction which eventually delivers a pentacyclic product. , Compound rac - 1 for example gave strained cyclopropanes rac - 2a and rac - 2b in a total yield of 62% (Scheme ).…”
mentioning
confidence: 99%